Analisis Pengelolaan Zakat di Arab Saudi, Indonesia dan Malaysia Sebagai Instrumen Keuangan Publik dan Sosial - Cindy Desnira; Ria Astuti; Alqurlia Ramadani; Heru Permana (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study aims to analyze and compare zakat management systems in Saudi Arabia, Indonesia, and Malaysia as instruments of public and social finance. The research employs a qualitative comparative method with a descriptive approach based on secondary data from official reports, academic literature, and regulatory documents. The findings reveal that Saudi Arabia applies a centralized and digitally integrated model under ZATCA, Malaysia implements a tax rebate system that directly reduces taxpayers' obligations, while Indonesia operates a decentralized collection system with zakat only treated as a gross income deduction. Saudi Arabia achieves a collection rate of approximately 85% of its estimated potential, Malaysia around 60-65%, and Indonesia only 6.87% of a potential of IDR 217.3 trillion. The study recommends that Indonesia adopt a hybrid integration framework combining Malaysia's fiscal incentive model and Saudi Arabia's digital efficiency to enhance compliance and optimize zakat's role in poverty alleviation and economic redistribution.